The rule of metaphor : the creation of meaning in language - Ricoeur, Paul; Czerny, Robert (London : Routledge, 2012)
First published in English in 1978, this comprehensive study of the philosophy of metaphor traces its development from Aristotle to the present. It brings together and analyzes key perspectives on metaphor from a range of disciplines, including linguistics and semantics, the philosophy of language, literary criticism, and aesthetics.
Includes bibliographical references and index.
Keywords: Language and languages - Philosophy; Meaning (Philosophy).; Metaphor - Philosophy; Metaphor in literature